Clear the fog: Can public–private collaborative supervision promote the construction of a high‐quality public health system? - Shen, Neng; Zhang, Jing; Cao, Yang Chun; Zhang, Lin; Zhang, Guoping (Managerial and decision economics, 2025)
Approaches to stimulating the initiative of collaborative cooperation of multiple subjects and the enthusiasm of public–private collaborative supervision are important to ensure the high‐quality development of the social public health system. This study constructs a four‐agent evolutionary game model with a medical enterprise, health administrative department, medical institution, and the social public as the core subjects. Using MATLAB 2018b to conduct simulation analysis, the cooperation strategy and operation mechanism of multiple subjects in the social public health system under public–private collaborative supervision are revealed, and the evolutionary stability strategy of multiple subjects under different situations is further explored. The results show (1) three evolutionary stability points in the system, which all exist in a state of loose government supervision. (2) Increasing the penalty limit can effectively regulate the behavior of medical enterprises and medical institutions; however, it is not conducive to the performance efficiency of the government in the long run. (3) Government incentives can stimulate the enthusiasm of all subjects to participate in the social public health system but should be controlled within a reasonable range. Excessive financial incentives make it easy for medical enterprises and institutions to form policy dependence.